2018
DOI: 10.21037/jtd.2018.10.41
|View full text |Cite
|
Sign up to set email alerts
|

Macrolide antibiotics in the treatment of chronic rhinosinusitis: evidence from a meta-analysis

Abstract: Background: The purpose of this study was to systematically assess the subjective and objective outcomes of macrolide therapy for chronic rhinosinusitis (CRS). Methods: PubMed, Embase and Cochrane databases were searched for clinical trials detailing the effects of macrolide therapy in patients with CRS and published up to December 2017. Sino-Nasal Outcome Test (SNOT), endoscopic scores and computed tomography scans (CT) scores were assessed by mean difference (MD) or standardized mean difference (SMD) with 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 31 publications
0
18
0
1
Order By: Relevance
“…However, the high antibiotic dose group (more than 29 days out of 90 days prior to ESS) was relatively less improved 1961 . In addition, macrolide therapy was reported effective 1105,1121,1962 . Moreover, several studies in CRSsNP patients have found that short term (9‐14 days) use of antibiotics improved clinical symptoms with no significant difference in several types of antibiotics 1102–1104 .…”
Section: Surgery For Chronic Rhinosinusitismentioning
confidence: 95%
“…However, the high antibiotic dose group (more than 29 days out of 90 days prior to ESS) was relatively less improved 1961 . In addition, macrolide therapy was reported effective 1105,1121,1962 . Moreover, several studies in CRSsNP patients have found that short term (9‐14 days) use of antibiotics improved clinical symptoms with no significant difference in several types of antibiotics 1102–1104 .…”
Section: Surgery For Chronic Rhinosinusitismentioning
confidence: 95%
“…Lasso et al pooled data from four RCTs and showed no difference between the effects of LDMs and placebo. The recent meta‐analysis by Shen et al included both randomized and nonrandomized controlled trials. Forest plots from the RCTs did not show the benefit of LDMs therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic modalities with established efficacy in bronchiectasis are also far from specific and beneficial in other airway diseases. Macrolides have proven efficacy in reducing exacerbations in CF [101], but also in diffuse panbronchiolitis [102,103], bronchiolitis obliterans in lung transplant recipients [104][105][106], COPD [107][108][109], CRS [110] and, recently, asthma [111]. Airway clearance and inhaled mucolytic agents, such as hypertonic saline, are the first-line treatment for CF [112].…”
Section: Bronchiectasis Is Heterogeneous and Comprised Of Many Differmentioning
confidence: 99%